OUTCOME OF DIETARY INTERVENTION ON WEIGHT AND ANTHROPOMETRIC INDICES OF OVERWEIGHT AND OBESE FEMALES: A RANDOMIZED CONTROLLED TRIAL: Anthropometric Indices of Overweight And Obese Females - Noreen, Khola; Khan, Shahzad Ali; Mashhadi, Syed Fawad; Rahman, Mahmood Ur; Ali, Syed Kashif (Pakistan Armed Forces Medical Journal, 2018)
Objective: To study impact of dietary intervention and counseling on weight and anthropometric indices of obese females. Study Design: Prospective randomized controlled trial. Place and Duration of Study: This study was conducted at Pakistan Navy Ship (PNS) Shifa, from Feb 2014 to Sep 2014. Patients and Methods: Study subjects were 320 obese females from Karachi, Pakistan, aged 20 to 40 years. Before randomization all baseline anthropometric measurements were recorded. After that females were randomly placed into intervention and control groups. Anthropometry and 24-hour dietary recall were used for nutritional assessment. Intervention strategy was individualized diet plan by registered dietitian according to base line body weight and anthropometric indices of study subject. Primary outcome was the change in body weight and body mass index. Results: The final analysis was run on 280 participants (intervention=127, control=153). Both intervention and control group were comparable with respect to anthropometric variables at start except intervention group had more body mass index (BMI) (28.024 ± 3.561). A significant change was observed in body weight (p=0.001), BMI (p=0.001), waist circumference (p=0.001), hip circumference (p=0.01), waist hip ratio (p=0.04) in an intervention group while control group only showed significant reduction in waist circumference (p=0.041). Intervention group showed significant improvement in dietary behavior which was depicted by increased intake of fruit and fiber consumption (p=0.001), reduction in consumption of simple carbohydrates (p=0.001), animal protein (p=0.001) and fatty food (p=0.001). Control group showed decrease in waist circumference in response to reduction in dietary fat intake and increase intake of fruits (p=0.001) and vegetables (p=0.042). Conclusion: The results of our study have positively demonstrated that nutritional intervention among obese females was successful in reducing weight and BMI. Reduction inwaist and hip circumference and change in diet behavior were also observed as secondary outcome variable.